Evaluation of Mechanical and Histological Significance of Nano Hydroxyapatite and Nano Zirconium Oxide Coating On the Osseointegration of CP Ti Implants - Majed Mohamed Refaat; Thekra Ismael Hamad (College of Dentistry/ University of Baghdad, 2016)
Background: Dental implant considers a unique treatment option for the replacement of missing dentition. The new trend of implants is looking for materials which accelerate bone formation in bone implant interface and enhance osseointegration to provide immediate loading directly after placement and decrease the time period which is disturbs patients and uncomfortable. The aim of the study was to evaluate the effect of nano zirconium oxide (ZrO2) and nano hydroxyapatite (Hap) mixture coating of screw shaped commercially pure titanium (cpTi) implants on bond strength at the bone implant interface with torque removal test and histological analysis in comparison with non coated implants. Materials and methods: Forty screws were machined from cpTi rods using a lathe machine. Then 20 screws coated by electrophoretic deposition method by a mixture of nano hydroxyl apatite and nano zirconium oxide, while the other 20 screws remain uncoated. The tibia of 10 adult white New Zealand experimental rabbits was chosen as implantation site, each rabbit tibia received 2 screws, one coated and the other uncoated. Torque removal test was performed to measure the torque required to remove the screw and histological analysis was performed to observe the new bone formation, after 2 and 4 weeks healing intervals. Results: Implant coated with a mixture of nano zirconium oxide and nano hydroxyl apatite showed a significantly higher removal torque values compared to uncoated one. There was more new bone formation with coated implants for both healing periods. Conclusions: Coating by electrophoresis considers a valuable process to coat metallic implants with a ceramic material and to form a uniform composite layer of coating. Osseointegration improved at bone-implant interface associated with the coated implants, which was illustrated by higher bone formation at the two intervals of time 2 weeks and 4 weeks.